Tumor vaccines with dsRNA adjuvant ARNAX induces antigen-specific tumor shrinkage without cytokinemia - Seya, Tsukasa (Oncoimmunology, 2015)
Here, we introduce a double-stranded RNA mimic that is chemically synthesized to exclusively stimulate toll-like receptor 3 (TLR3). This function-defined TLR3 ligand, named ARNAX, acts as an adjuvant to induce antitumor CTL and NK without significant cytokinemia in mice, and thus superior to polyI:C for therapeutic vaccine immunotherapy against tumor.